Elucidating anomalous protein diffusion in living cells with fluorescence correlation spectroscopy: facts and pitfalls - Malchus, Nina; Weiß, Matthias (Journal of fluorescence, 2010)
Anomalous protein diffusion has been frequently observed in intracellular fluids and on membranes of living cells. Indeed, a large variety of specimen, from bacteriae to mammalian cells, and several non-invasive measurement techniques, e.g. fluorescence correlation spectroscopy, have revealed that the mean square displacement (MSD) of proteins in vivo is often characterized by an anomalous power-law increase ⟨r(t)2⟩∼tα with 0.5 < α ≤ 0.8. Here, we review these results with a particular focus on fluorescence correlation spectroscopy, and we report on possible causes of variations of the anomaly degree α. Moreover, we highlight generic consequences of anomalous diffusion that are likely to play an important role in the cellular context.